The Foresight Study of Virtual Reality as An Advertising Tool - Syed Azman, Syed Muhammad Farhan; Ahmad, Nurazwa (Research in Management of Technology and Business, 2021)
Virtual Reality (VR) is a technology that provides users with a whole new experience by immersing them into a virtual world. Based on previous study made by researchers, they have found that VR has many advantages compared to disadvantages. However, little study has been found regarding virtual reality as an advertising tool since the technology is still in its early stages. The purpose of this study if to identify issues and drivers thus determining the future with this technology. This study uses future wheel implication and uses both qualitative and quantitative method. STEEPV analysis will be used to identify key drivers of the technology and analyze the data using SPSS. Return rate of the questionnaire was 15.63% which was 60 out of 384 questionnaires distributed. The data was collected through online questionnaires. The highest key drivers of the technology are growth of VR users, increased brand recognition and brings emotional value. The least discussed drivers would be regarding the environment. The future predictions will be made using Future Wheel analysis to determine future implication of Virtual Reality as an Advertising Tool. The top two drivers from impact-uncertainty analysis were “Advertising in VR will increase brand recognition due to the creative advertisement.” and “Virtual Reality enables users to explore places and contents without having to physically being there.” Based on the two top drivers, the predictions made using future wheel analysis were market leaders in advertising, increase brand recognition, promotes innovation and greater immersion. These predictions gave out positive implication towards the technology in the future. Suggestions made to improve this study were to increase duration of data collection. This enables more accurate response from consumers. VR provides promising impact towards advertising in the future that will improve current advertising.